Public Sector Support for Innovations - Keita, Mariama (Univerzita Pardubice, 2019)
This research was about public sector support for innovations. To establish the critical role of the public sector in the innovative changes taking place currently around the world. The role of the public sector in supporting innovation not only within, but also most importantly in the private sector was investigated on the basis of the three fundamental functions of the public sector as postulated by Rajeswari (1998, p.1). To extensively investigate this phenomenon, the research approached the subject matter through analytic research approach. Highlighting the different ways, the public sector supports innovations within and in the private sector. Using the Schumpeter's theory on dimensions of innovation as the principal theoretical underpinning for the research. The significance of public sector support for innovation was investigated first from the happenings with the supranational body, the EU. Identifying the role of finances in determining the importance of policy. Then the EU policies on innovation and its scope were examined. Highlighting the financial commitments of the EU to each of its policy programme. The research then conducted a comparative analysis of two of the countries within the EU as a sample of the entire population of individual EU member states to evaluate how their public sector is supporting innovations within and also in the private sector. The Czech Republic and the German Democratic Republic were purposively chosen because of their near opposite standing in terms of economic status and political standing within the EU. The Czech Republic representing the small member states and Germany, the big EU states. Using mainly secondary research data, the research concludes that the EU takes the participation of the public sector supporting innovation seriously. It also concludes that while the Czech Republic and Germany have different experiences in terms of their relationship with public sector support for innovations. And their approaches also been different. The two focal sample states and the EU have two central agreements that are common to all. First, the irreplaceability of the public sector as a catalyst for innovations in any nations. Two, the central role of shared data, cooperation and coordination amongst all entities involved in the pursuit of innovations.
Keywords: veřejný sektor; soukromý sektor; inovace; výzkum a vývoj; technologie; public sector; private sector; innovations; research and development; technology